Zdvořilý řečový habitus jako sociokulturní regulativ vztahové sítě III.: Vnitřní pořádek řečové hry - Slowik, Miroslav (Lidé města, 2024)
This study deals with politeness in speech, which is governed by a language code, and attempts to find a definition for this complex, multidisciplinary concept, as well as to perceive it as a human structure that takes on the form of a game. Through politeness, the language game allows the interaction of speakers, who thus carry out a limited number of transactions, hence confirming the categorisation of their world and simultaneously maintaining those social values that transform into the national behavioural prototype. This language game is based on specific game principles that stem from a concrete, imagined social order, cemented into a national/nationalistic whole by the ethnic language. The article attempts to summarise in general these basic game principles, and then shows the inner logics of the language market that is dominated by a specific game structure on concrete examples in Czech and Spanish.